Pengaruh Media Pembelajaran Dan Sikap Bahasa Terhadap Berbicara Bahasa Inggris - Sukmono Bayu Adhi (LPPM Universitas Bina Sarana Informatika, 2015)
This study aimed at analyzing the effect of using pictures as the teaching media and language attitude towards students’ speaking skill at secondary school level. It was an experimental research which used 2x2 factorial design. The population was 5 classes (consisted of 32 students in each class) of grade IX Madrasah Tsanawiyah Annajah Jakarta Selatan in academic year 2013/2014 in which 40 students were chosen as the sample of this research. The data collected by spreading the questionaire out to the sample and giving the test. The data in this study was analyzed by using statistical 2-Way Anova (Analysis of Variance) and Tukey Test. The research finding were first, there was a significant effect of the using pictures as the teaching media toward students’ English speaking skill based on the result from ANOVA table, where p-value for teaching media was 0.000 which was less than 0.05 or sig 0.000 < 0.05. Second, there was no influence of language attitude toward students’ English speaking skill based on the p-value both positive and negative sig = 0.165 > 0.05. Third, there was no significant interactional effect between the use of pictures as the teaching media and language attitude toward the students’ speaking skill based on p-value which is sig = 0.254 > 0.05.